2023
DOI: 10.3390/su15086383
|View full text |Cite
|
Sign up to set email alerts
|

Land Degradation–Desertification in Relation to Farming Practices in India: An Overview of Current Practices and Agro-Policy Perspectives

Abstract: Land degradation and desertification (LDD) has gained worldwide policy attention due to decline in land quality and the resultant economic burden accrued upon a vast population reliant on land-based natural capital. In India, the impacts are becoming apparent as 24 out of 29 states have been experiencing LDD since the early 2000s. Here, we adopt a mixed-method approach combining hierarchical cluster analysis (HCA) and multilinear regression analysis (MLRA) with contextual assessments to draw on, using state-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…To that end, we believe that much of the success hinges upon how well the new leadership melds different spheres of development: (a) social and economic, (b) technological innovation and (c) environmental systems' governance (Figure 5). The idea is to imagine an inclusive system's governance, founded on an ecosystem of stakeholders, within a sphere of participatory action (Chaudhuri et al, 2020(Chaudhuri et al, , 2023(Chaudhuri et al, , 2024(Chaudhuri et al, , 2021b. Potential stakeholders may include (but are not limited to), the public agencies, development organisations, financial institutions, think tanks, research groups, NGOs, intergovernmental organisations, universities/technical education centres/research organisations, UN offices and any other that could potentially help develop sound mining/mineral exploration protocols.…”
Section: Forging a Multidimensional Ecosystemmentioning
confidence: 99%
“…To that end, we believe that much of the success hinges upon how well the new leadership melds different spheres of development: (a) social and economic, (b) technological innovation and (c) environmental systems' governance (Figure 5). The idea is to imagine an inclusive system's governance, founded on an ecosystem of stakeholders, within a sphere of participatory action (Chaudhuri et al, 2020(Chaudhuri et al, , 2023(Chaudhuri et al, , 2024(Chaudhuri et al, , 2021b. Potential stakeholders may include (but are not limited to), the public agencies, development organisations, financial institutions, think tanks, research groups, NGOs, intergovernmental organisations, universities/technical education centres/research organisations, UN offices and any other that could potentially help develop sound mining/mineral exploration protocols.…”
Section: Forging a Multidimensional Ecosystemmentioning
confidence: 99%
“…These changes include shifts in rainfall up to 6mm and alterations in the duration and onset of the rainy season. Consequently, water scarcity is Forests at the Crossroads: Biodiversity Conservation in the Era of Climate Change DOI: http://dx.doi.org/10.5772/intechopen.1004224 expected to amplify, intensifying the risk of land degradation [58,60,61]. Such climatic shifts pose a profound risk to the biodiversity of Sudan's drylands, diminishing ecosystem productivity and leading to losses in species diversity, ecosystem functions, and vegetation variety [58,62].…”
Section: Impacts Of Climate Change On Biodiversitymentioning
confidence: 99%
“…Water evaporation and lake area decrease, vegetation habitat is reduced, plant growth is inhibited, and the vegetation coverage area is reduced. Vegetated areas are sensitive to precipitation [64], and the change in the vegetation landscape follows the change trend of precipitation. In a study on the response of vegetation coverage to precipitation changes in typical sandy land in eastern China, Kaymaz et al [65] confirmed this point [66].…”
Section: Driving Mechanism Of Vegetation-lake-sand Landscape Evolutionmentioning
confidence: 99%